Contemporary Dangers in Researching the Field in the Republic of Srpska in Retrospect to the Yugoslav War in Bosnia and Herzegovina: An Experience from the Field in the Area of Kozara and Potkozarje - Nikola Petrović (Conversations Across the Field of Dance Studies)
In May 2019, Nikola did his fieldwork in the Kozara-mountain and Potkozarje-area (northwestern Republic of Srpska/Bosnia and Herzegovina), researching the traditional folk dances, songs, music and customs from the Serbian population. During his research, he noticed and was told that many dances and songs were influenced by the Serbian and Croatian population from Croatia (Slavonija- and Banija-region). After he tried to conduct a further research on these influences, he was met with nationalistic and chauvinistic remarks against the Croatian and Muslim population in the area and the Republic of Croatia in general, even though the Serbian population was discussed. The research on that day was nearly cancelled from the side of the informants. This audio-exchange (including materials from the field) should give insights on the (political) mentality of the population after the Yugoslav wars and dangers of conducting research in this area, when talking about the three major ethnic groups.